Distorsi citra tubuh, perilaku makan, dan fad diets pada remaja putri di Yogyakarta - Atika Sulistyan; Emy Huriyati; Janatin Hastuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2016)
Background: Vast changing environment and culture including mass media which commonly shows models with a very slim body may cause teenage girls feel fatty and not confident despite their normal body weight. This misperception may influence eating behavior and encourage them to lose weight by involving in some instant diets, for example, fad diets.Objective: To identify relationships between body image distortion, eating behavior, and fad diets among female adolescents in Yogyakarta.Method: This study was a cross-sectional study on 123 school girls at SMAN 8 Yogyakarta who have normal body mass index (BMI) according to WHO category. Body image distortion and eating behavior were evaluated using the Body Image Assesment-Body Dimension (BIAS-BD), and the Eating Attitude Test (EAT)-26, respectively. Fad diets were assessed using a questionnaire adapted from Hana (10) and Rafiqa (11). The hypotheses were tested using chi-square test and Spearman’s correlations.Results: As many as 105 girls (85.4%) showed body image distortion and 15 girls (12.2%) were at risks for having disordered eating behavior. Among 51 girls (42.5%) who experienced or tried to lose weight, 47 girls (92.2%) were practicing fad diets. There was no significant association between body image distortion and disordered eating behavior, nor between body image distortion and fad diets. However, disordered eating behavior was significantly associated with fad diets with OR = 7,077 (p<0.05).Conclusion: There was a significant relationship (p<0.05) between disordered eating behavior and fad diets, however, no significant association was found between body image distortion and disordered eating behavior, and between body image distortion and fad diets among female adolescents in Yogyakarta.